PyPhotonics: A python package for the evaluation of luminescence properties of defects - Tawfik, Sherif Abdulkader; Russo, Salvy P. (Computer physics communications, 2022)
The prediction of the photoluminescence line-shape of defect systems from first principles is becoming an important tool for the discovery of quantum emission defects in semiconductors. Using a sequence of density functional theory calculations based on the VASP code, PyPhotonics calculates the Huang-Rhys factor and plots the photoluminescence line-shape of the defect by processing the VASP output. Program title: PyPhotonics CPC Library link to program files:https://doi.org/10.17632/vy4ccz4hxz.1 Developer's repository link:https://github.com/sheriftawfikabbas/pyphotonics Licensing provisions: GNU General Public License 3 Programming language: Python 3.9 Nature of problem: While density functional theory (DFT) codes can calculate properties of crystal defects, there are no available codes to calculate the photoluminescence line-shape and the Huang-Rhys factors for the defects computed using DFT. Solution method: The PyPhotonics python code is a post-processing library written entirely in python, which takes as input the output files of the VASP and phonopy codes for a defect system, and calculates the Huang-Rhys factor and the PL lineshapes for that system.